Thinking aesthetically 10 years of Sahrdaya - Amaladass Anand (Chennai Satya Nilayam, 2002)
The collection of short essays reflects the well-meaning seekers of truth to various themes related to life and art, aesthetics and formation, art and worship, art and healing, art and feminine,etc.
Keywords: Aesthetics; Art